(1 + cot A + tan A) (sin A - cos A) = sin A tan A - cot A cos A
Answer:
see explanation
Step-by-step explanation:
Using the trigonometric identities
tan A = , cot A =
Consider the left side
(1 + cotA + tanA)(sinA - cosA)
each term in the second factor is multiplied by each term in the first factor.
1(sinA - cosA) + cotA(sinA - cosA) + tanA(sinA - cosA)
= sinA - cosA + cosA - + - sinA ( collect like terms )
= -
= ( sinA × ) - ( × cosA )
= sinAtanA - cotAcosA
= right side ⇒ proven
Answer:
39°
Step-by-step explanation:
Internal angles of the triangle are:
Angle x is:
Answer:
3"x4
Step-by-step explanation:
The symbol for a foot is "ft", sometimes denoted by a prime(') , also, the inch is denoted by a double prime(").
Given
2 1/2inces (2.5") blue print represents 10ft living room
We are told that the dimension of the room on the blueprint is
12'x16'
Let us convert 12' to inches
So
2.5" represents 10'
X ' will be 12'
Cross multiplying
X=(2.5*12)/10
X=3"
Let us convert 16' to inches
So
2.5" represents 10'
Y ' will be 16'
Cross multiplying
Y=(2.5*16)/10
Y=4"
the dimension of the blue print is
3"x4"
Hi there!
To solve, let's rewrite this equation.
Step 1) Simplify both sides of the equation.
(Distribute)
(Combine Like Terms)
Step 2) Add 2 to both sides.
Step 3) Divide both sides by 2.
Final Answer -
Hope this helps!
Message me if you need anything else, I'd be happy to help you! :D
Answer:
36:24
Step-by-step explanation:
6+4=10
60/10=6
6*6:4*6
=36:24